Ceramic membrane preparation from waste : effect of additive: article - Rosli, Faten Nur Amanina; Ibrahim, Norliza (2017)
Ceramic support is the most basic layer of a ceramic membrane. A ceramic membrane plays a vital role in filtration especially. Usually ceramic membrane is artificial and its made up of inorganic materials such as alumina, titania, zirconia oxides, silicon carbide or some glassy materials. In this experiment, ceramic waste from Top Glove Sdn Bhd is obtained and crushed to become tiny particles. The crushed ceramic is then sieved to obtain a diameter range of less than 180 microns. Using compression method, these materials are prepared to produced circular pellets in which characterization will be tested based on the composition structure of the materials upon adding different composition of additives, MoO₃ and AlF₃.